POLARIZATION HYSTERESIS CURVE MEASUREMENT FOR AN Au/PZT/YBCO DEVICE BY DOUBLE PULSE TECHNIQUE (Journal of Sciences, Islamic Republic of Iran)
Polarization for Au/Pb(Zr Ti )O /YBa Cu O ferroelectric capacitor has been studied and measured by pulse method. A sequence of pulses with amplitudes varying from 0 to 10 volts in 2 volt steps is applied and a conventional polarization curve is obtained by integrating the charge flow from the polarization switching induced by the voltage ramp. A value of 25?C/cm2 is measured for the saturated polarization from the hysteresis curve. The polarization retention is also measured at 200°C for the device and the polarization change over 24 hours was about 5.7%.